DOI: 10.31274/etd-180810-5035
|View full text |Cite
|
Sign up to set email alerts
|

Predicting academic major satisfaction using environmental factors and self-determination theory

Abstract: Environmental factors (faculty integration and student integration) and self-determination theory factors (perceived autonomy, perceived competence, and perceived relatedness) were used to predict academic major satisfaction. It was hypothesized that environmental factors and self-determination factors would directly predict major satisfaction. In line with this, it was predicted that a path model which included environmental factors would prove to be a better fit than a model that did not. It was also predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(150 reference statements)
0
3
0
Order By: Relevance
“…Sovet et al (2015) found that AMS was correlated to life satisfaction among college students. In another study, AMS was associated with positive outcomes among students' current and future outcomes (Schenkenfelder, 2017). This follows that when students feel gratified with their selected major and gain confidence from good academic results, they are less likely to drop out (Nauta, 2007).…”
Section: The Mediation Effect Of Academicmentioning
confidence: 90%
“…Sovet et al (2015) found that AMS was correlated to life satisfaction among college students. In another study, AMS was associated with positive outcomes among students' current and future outcomes (Schenkenfelder, 2017). This follows that when students feel gratified with their selected major and gain confidence from good academic results, they are less likely to drop out (Nauta, 2007).…”
Section: The Mediation Effect Of Academicmentioning
confidence: 90%
“…Consistent with this, academic major satisfaction, which indicates one's satisfaction with her/his choice of major, has been suggested as a potential predictor of life satisfaction among college students (Nauta, 2007). It has been found to predict positive current and future academic outcomes, such as a decreased dropout rate (Nauta, 2007) and an increased grade point average (GPA; Leach & Patall, 2013;Nauta, 2007), which have also been linked to increased life satisfaction among college students (e.g., Chow, 2005;Schenkenfelder, 2017).…”
mentioning
confidence: 83%
“…The construct has emerged with significant implications for career development (Deemer, 2015) as it has been found to be positively associated with academic performance (Graunke & Woosley, 2005;Nauta, 2007), intrinsic motivation for a subject (Deemer, 2015), career decision self-efficacy (Jadidian & Duffy, 2012;Nauta, 2007) and work volition (i.e., feeling that one is able to make her/his own occupational decisions despite barriers; Jadidian & Duffy, 2012). Research has also found that occupational engagement (Cox, Bjornsen, Krieshok, & Liu, 2015), self-regulated learning engagement (Kim & Kim, 2016) and perceived competence (Schenkenfelder, 2017) are positively associated with academic major satisfaction. Another study found identity (i.e., the extent to which one has a clear sense of goals, interests and abilities), a construct that is important in Holland's vocational theory identity, to be a significant positive predictor of academic major satisfaction among students majoring in music (Allen, 1996).…”
Section: Academic Major Satisfactionmentioning
confidence: 99%